(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The research aims to study the role of entrepreneurial leadership in achieving institutional excellence in Saudi universities, considering the rapid challenges and changes in the higher education sector. It also seeks to analyze the suitability of entrepreneurial leadership for Saudi universities and its impact on institutional performance, focusing on its key elements such as creativity, initiative, and calculated risk-taking. The study adopted a descriptive-analytical approach, analyzing previous literature on entrepreneurial leadership, examining global university experiences, and exploring entrepreneurial leadership practices in some Saudi universities. Additionally, it analyzed institutional excellence standards, including effective leadership, strategic planning, and strengthening community partnerships. The findings indicate that the implementation of entrepreneurial leadership in Saudi universities is still in its early stages. However, efforts are being made to enhance it through various initiatives and development programs. The study also identified key challenges hindering the adoption of entrepreneurial leadership, including insufficient funding, institutional resistance to change, a lack of trained leadership competencies, and unclear policies supporting entrepreneurship. The recommendations emphasize establishing specialized units within universities to support entrepreneurial leadership, developing training programs for academic leaders to enable them to adopt entrepreneurial strategies, enhancing creativity, initiative, and calculated risk-taking by establishing specialized centers within universities to support entrepreneurial ideas and finance academic and research projects focused on innovation and development, and integrating technology and artificial intelligence into entrepreneurial leadership practices to enhance institutional performance efficiency and achieve global leadership.